Analisis Data Peserta Didik Sekolah Menengah Atas (SMA) Menggunakan Visualiasasi Google Looker Studio - Oktaviani, Fenny; Nita Rosa Damayanti (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2024)
Google Looker Studio, previously known as Google Data Studio, is one of the data visualization tools that can make it easier to manage such data. Looker Studio allows users to integrate data from various sources, analyze it, and present it in an interactive and easy-to-understand visual form. Using Google Looker Studio, schools can create reports and dashboards depicting learner data in real-time, facilitating effective analysis and reporting. This study concludes that Google Looker Studio is an effective and efficient tool for learner data visualization in high schools. It helps in data processing and analysis and supports faster and evidence-based decision-making. Users perceived significant benefits in terms of efficiency with a result of 85%, data understanding of 78%, and reporting quality of 82%, so Looker Studio has great potential to be applied more widely in educational settings.